Developing a framework of Muslim consumer religiosity, brand preferences and purchase intention of halal food products in Malaysia / Johari Abdullah - Abdullah, Johari (2023)
Religiosity is an element of culture which is crucial in understanding individual preferences and intentions related to religion. It consists of religious belief, social and environmental responsiveness, norms and knowledge that influence human behaviour. Over the years, studies have relied on specific frameworks to explain related behaviour to understand the impact of religiosity. However, due to shortfalls in these frameworks, they may not be a complete basis to assess Muslim consumers, especially in their intentions to purchase Halal food products. Researchers assume that universal religiosity instruments are relevant across different religions and fields of study, but these instruments might not suit all frameworks. As a result, it may not be possible to adequately reflect nor explain religiosity factors for Muslim consumers. It also create the gap in understanding Muslim consumers from practitioners perspective in catering products that parallel their religiosity. This thesis aims to propose a new framework to fill these gaps. Muslim consumer religiosity is identified and its impact on purchase intention and brand preferences is assessed using an exploratory sequential mixed method research design. This includes employing qualitative and quantitative procedures such as Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and assessments of relationships among these factors based on two separate data collections involving 1127 Muslim consumers in Malaysia. Data collection 1 of 600 samples were focused on EFA and 527 samples were used for CFA utilizing Structural Equation Modelling (SEM). The results indicated five factors of Muslim consumer religiosity, namely religious belief, norms, environmental responsiveness, knowledge, and social responsiveness that constitute the newly developed Muslim Consumer Religiosity Scale (MCRS). The path coefficient analysis revealed that religious belief and environmental responsiveness directly affect purchase intention. However, norms, environmental responsiveness, and knowledge were not significant. Mediation analysis indicated that brand preferences partially mediate the relationship between religious belief and purchase intention but fully mediate the relationship between social responsiveness and purchase intention. The proposed RELBRAINT framework highlights six strategies for understanding Muslim consumers through religiosity, purchase intention and brand preferences. In conclusion, this study argues that multidimensional consumer religiosity can be compatibly incorporated into the RELBRAINT framework. Therefore, this study enriches the body of knowledge on Muslim consumers concerning their religiosity, brand preferences and purchase intention of Halal food products